Defining Textbook Outcome in liver surgery and assessment of hospital variation: A nationwide population-based study. Issue 12 (December 2022) - de Graaff, Michelle R.; Elfrink, Arthur K.E.; Buis, Carlijn I.; Swijnenburg, Rutger-Jan; Erdmann, Joris I.; Kazemier, Geert; Verhoef, Cornelis; Mieog, J. Sven D.; Derksen, Wouter J.M.; van den Boezem, Peter B.; Ayez, Ninos; Liem, Mike S.L.; et al.
Abstract: Introduction: Textbook outcome (TO) is a composite outcome measure covering the surgical care process in a single outcome measure. TO has an advantage over single outcome parameters with low event rates, which have less discriminating impact to detect differences between hospitals. This study aimed to assess factors associated with TO, and evaluate hospital and network variation after case-mix correction in TO rates for liver surgery. Methods: This was a population-based retrospective study of all patients who underwent liver resection for malignancy in the Netherlands in 2019 and 2020. TO was defined as absence of severe postoperative complications, mortality, prolonged length of hospital stay, and readmission, and obtaining adequate resection margins. Multivariable logistic regression was used for case-mix adjustment. Results: 2376 patients were included. TO was accomplished in 1380 (80%) patients with colorectal liver metastases, in 192 (76%) patients with other liver metastases, in 183 (74%) patients with hepatocellular carcinoma and 86 (51%) patients with biliary cancers. Factors associated with lower TO rates for CRLM included ASA score ≥3 (aOR 0.70, CI 0.51–0.95 p = 0.02), extrahepatic disease (aOR 0.64, CI 0.44–0.95, p = 0.02), tumour size >55 mm on preoperative imaging (aOR 0.56, CI 0.34–0.94, p = 0.02), Charlson Comorbidity Index ≥2 (aOR 0.73, CI 0.54–0.98, p = 0.04), and major liver resection (aOR 0.50, CI 0.36–0.69, p < 0.001). After case-mix correction, no significant hospital or oncological network variation was observed. Conclusion: TO differs between indications for liver resection and can be used to assess between hospital and network differences.